Office workers' beliefs about reducing sitting time at work: a belief elicitation study. Issue 1 (1st January 2018) - Niven, Ailsa; Hu, Dan
ABSTRACT: Objectives: Prolonged sitting has adverse health consequences, yet office workers can spend over 10 hours sitting each day. The Theory of Planned Behaviour may offer a useful perspective for understanding and enhancing psychological determinants of sitting at work. The aim of this belief elicitation study was to identify office workers' most salient beliefs relating to achieving the recently published Public Health England recommendation of accumulating at least two hours per day of standing and light activity at work. Methods: Full-time office-based workers ( n  = 105) responded to our invitation on Twitter to complete an on-line questionnaire. Participants responded to six open-ended questions about their behavioural (i.e. advantages/disadvantages), normative (i.e. who would approve/disapprove), and control (i.e. easy/difficult) beliefs relating to the target behaviour, and the data were content analysed to identify the most salient themes. Results: The most salient advantage of the behaviour was better health ( n  = 243), and most salient disadvantage was decreased work productivity ( n  = 64). Participants believed that people in work with a remit for health ( n  = 34) were likely to approve of the behaviour, but that managers ( n  = 68) would be likely to disapprove. It was believed that a better physical environment ( n  = 75) would make it easier, and work demands ( n  = 102) would make it difficult to execute the behaviour. Conclusions: Although participants recognised many benefits of engaging in the behaviour, there was consistent evidence that participants believed the behaviour may have implications for working effectively, and would be influenced by the physical environment and work culture. Interventions should target these salient beliefs.